INTERPRETATION OF THE IMAGE OF AMERICAN PHILOSOPHICAL SCHOOLS IN THE P. V. KOPNIN’S VIEWS - Varganov, Anton (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2022)
The article is devoted to the interpretations of the images of American schools that existed in Soviet philosophy, especially in the views of the founder of the Kyiv school of philosophy P. V. Kopnin. The relevance of the study is due to the views of the perception of American philosophical schools by the Soviet tradition since modern ideas about the history of American philosophy are largely based on these ideas. Through their own research and peculiarities of perception, the outstanding Soviet philosophers of the Kyiv school developed a paradigmatic vision of the historical and philosophical context of the existence of a particular school. Turning into weight certain features and aspects of individual historical and philosophical phenomena and carrying out a subjective interpretation, P. V. Kopnin formed his own understanding of their essence, developing further guidelines for future philosophical studies of his followers. The study of the results of these interpretations allows, on the one hand, to better understand the vision of the Soviet philosophy of the history of American philosophy, on the other hand, through the prism of this understanding, with the possibility of overcoming it, to explore American philosophical schools from a different angle and to carry out their own interpretation of these images.